Gender-responsive genomic selection on farmer’s fields for accelerating genetic gains - Nchanji, Eileen Bogweh; Mamo, Teshale Assefa; Birachi, Eliud Abucheli; Lutomia, Cosmas Kweyu; Yao, Kouadio Nasser; Mlalila, Fabiano (2023)
This study used gender-intentional participatory approaches to address the challenges of low genetic correlation and lower genetic gains for small-scale bean producers in sub-Saharan Africa. The differences between on stations and on-farm performance of bean varieties in sub-Saharan bean farming, especially for women farmers with limited resources, may cause low genetic correlation and lower genetic gains for small-scale producers. Traditional breeding methods take several years and costly, making it challenging to meet evolving farmer needs. The study employs gender-intentional participatory approaches to address these challenges, incorporating women's preferences and production environments from the early stages of variety development. We know that men and women farmers often have different trait preferences influenced by gender roles and knowledge, and capturing these gender and socioeconomic differences is crucial for accelerating genetic gains on farm. In addition, gender and socioeconomic data are needed to guide breeding at the design stage of any breeding program.